PENGARUH KARAKTERISTIK INOVASI DAN SISTEM SOSIAL TERHADAP TINGKAT ADOPSI TEKNOLOGI PENGELOLAAN TANAMAN TERPADU (PTT) PADI DI KECAMATAN KEBAKKRAMAT KABUPATEN KARANGANYAR - Nurmastuti, Ardela; suminah, suminah; Wibowo, Agung (AGRITEXTS: Journal of Agricultural Extension, 2017)
This study examines to find out the influence of characteristic innovation and social system toward the adoption rate of Integrated Crop Management (PTT) technology of rice in Kebakkramat Sub District Karanganyar Regency. The basic method of research is explanatory method with survey technique. The location of study was determined purposively in Kebakkramat Sub-district of Karanganyar Regency with the consideration that Kebakkramat Sub District is one of the sub-districts implementing Integrated Crop Management (PTT) program and the sub district has the lowest rice productivity among the two other sub districts namely Tasikmadu and Jaten Sub Districts implementing GP-PTT in Karanganyar Regency. The sampling method used is proportional random sampling, with a sample size of 60 farmers. Data analysis using path analysis. The results showed that: (1) there is significant influence between characteristic innovation, social system and motivation simultaneously toward adoption of integrated crop management innovation. (2) there is significant influence between characteristic innovation toward adoption of integrated crop management innovation greater if it is compared through motivation, there is significant influence between social system toward adoption of integrated crop management innovation greater if it is compared through motivation and there is significant influence between motivation to adoption of integrated crop management innovation.